Xenodiagnosis to Detect Borrelia burgdorferi Infection: A First-in-Human Study - Marques, Adriana; Telford, Sam R.; Turk, Siu-Ping; Chung, Erin; Williams, Carla; Dardick, Kenneth; Krause, Peter J.; Brandeburg, Christina; Crowder, Christopher D.; Carolan, Heather E.; Eshoo, Mark W.; Shaw, Pamela A.; et al. (Clinical infectious diseases, 2014)
Background. Animal studies suggest that Borrelia burgdorferi, the agent of Lyme disease, may persist after antibiotic therapy and can be detected by various means including xenodiagnosis using the natural tick vector (Ixodes scapularis). No convincing evidence exists for the persistence of viable spirochetes after recommended courses of antibiotic therapy in humans. We determined the safety of using I. scapularis larvae for the xenodiagnosis of B. burgdorferi infection in humans. Methods. Laboratory-reared larval I. scapularis ticks were placed on 36 subjects and allowed to feed to repletion. Ticks were tested for B. burgdorferi by polymerase chain reaction (PCR), culture, and/or isothermal amplification followed by PCR and electrospray ionization mass spectroscopy. In addition, attempts were made to infect immunodeficient mice by tick bite or inoculation of tick contents. Xenodiagnosis was repeated in 7 individuals. Results. Xenodiagnosis was well tolerated with no severe adverse events. The most common adverse event was mild itching at the tick attachment site. Xenodiagnosis was negative in 16 patients with posttreatment Lyme disease syndrome (PTLDS) and/or high C6 antibody levels and in 5 patients after completing antibiotic therapy for erythema migrans. Xenodiagnosis was positive for B. burgdorferi DNA in a patient with erythema migrans early during therapy and in a patient with PTLDS. There is insufficient evidence, however, to conclude that viable spirochetes were present in either patient. Conclusions. Xenodiagnosis using Ixodes scapularis larvae was safe and well tolerated. Further studies are needed to determine the sensitivity of xenodiagnosis in patients with Lyme disease and the significance of a positive result. Clinical Trials Registration. NCT01143558.